Strategi Humas dalam Meningkatkan Kualitas Pelayanan Administrasi Publik Melalui KUBERSERI di Kecamatan Plumpang Kabupaten Tuban - Junita Nurul Hidayah; Durinta Puspasari (Concept: Journal of Social Humanities and Education, 2024)
This research aims to analyze public relations strategies to improve the quality of public administration services through KUBERSERI in Plumpang District. The research method used is a qualitative descriptive method. The data sources used are primary and secondary data sources. Data collection techniques in this research are interviews, observation and documentation. Data analysis in this research includes data collection, data reduction, data presentation, and drawing conclusions. The theoretical basis used in this research is the Cutlip, Center & Broom theory, namely that there are 4 indicators of public relations strategy, including fact finding (situation analysis), planning, action and communication (action and communication), and evaluation (evaluation). And for service quality variables, a theory is used which consists of 5 indicators, namely tangibles, reliability, responsiveness, assurance and empathy. The results of the research show that Plumpang District has implemented a strategy to improve the quality of administrative services well. Although in general Plumpang District has implemented efforts or strategies to improve the quality of its services, there are still several indicators that need to be improved in order to influence the community's expectations of obtaining quality services in Plumpang District.